2013
DOI: 10.1038/pcan.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on clinicopathological outcome and biochemical recurrence after radical prostatectomy

Abstract: BACKGROUND: Accumulating evidence suggests that obesity is associated with tumor progression in prostate cancer (PCa) patients after radical prostatectomy (RP). We conducted a retrospective multicenter study to determine the effect of body mass index (BMI) on the clinicopathological characteristics and biochemical recurrence of PCa in Japanese men who underwent RP. METHODS: The medical records of 1257 men with PCa treated by RP without neoadjuvant therapy at four medical institutes between 2001 and 2009 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
0
9
1
Order By: Relevance
“…In Asian patients, the adverse pathological findings of PCa may be attributable to obesity according to previous reports (18,19). However, other reports have not demonstrated any association of obesity with the clinicopathological characteristics of PCa (20,21). Such conflicting results may be explained by the different distribution of BMI among countries.…”
Section: Univariate Analysis Multivariate Analysis ------------------contrasting
confidence: 41%
See 1 more Smart Citation
“…In Asian patients, the adverse pathological findings of PCa may be attributable to obesity according to previous reports (18,19). However, other reports have not demonstrated any association of obesity with the clinicopathological characteristics of PCa (20,21). Such conflicting results may be explained by the different distribution of BMI among countries.…”
Section: Univariate Analysis Multivariate Analysis ------------------contrasting
confidence: 41%
“…Although obesity in Asian countries is less severe compared with that in western countries, certain studies have suggested an association between BMI and PCa, including pathological characteristics (18,19). However, the effect of obesity on PCa-related mortality has been controversial, and it remains unclear whether obesity contributes to the aggressiveness of PCa in Asian patients (20,21). The aim of the present study was to investigate the association between BMI and the clinicopathological characteristics of PCa, and determine whether obesity increases the risk of biochemical recurrence after radical prostatectomy (RP) in Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, most Asian countries have experienced a boom in the incidence and mortality rate of PCa [ 7 ], which has been generally attributed to a Westernised life style, elevated body weight and increased prostate biopsy rates in Asian populations. Meanwhile, previous studies in Asian populations have drawn contradictory conclusions that BMI had positive, null or negative impacts on the risks of PCa and HGPCa [ 8 11 ]. Recently, Masuda et al reported higher rates of PCa and HGPCa detection in patients with a BMI <21 kg/m 2 compared to those with a BMI from 21–22.9 kg/m 2 in Japanese men [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously established a multicenter retrospective database of PCa patients who received radical prostatectomy at four institutions in the Tohoku district of Japan to assess the outcome and problems associated with radical surgery without any neoadjuvant treatments for localized PCa . Here, we investigated the effects of various clinical and pathological factors on BCR‐free survival in D'Amico intermediate‐risk patients, and tried to re‐stratify patients with intermediate‐risk PCa into two groups according to BCR, after radical prostatectomy, using our multicenter database.…”
Section: Introductionmentioning
confidence: 99%